Howard Thurman : Philosophy, Civil Rights, and the Search for Common Ground - Jensen, Kipton E. (Book collections on Project MUSE., 2019)
"In the following chapters, I examine Howard Thurman's thought as a philosopher: this claim constitutes both a fact about who I am-as a reader of Thurman and as someone classically trained as a philosopher, as someone attuned to the philosophical allusions and the ontological meaning of what Thurman wrote-and an expression of a modest philosophical thesis and an interpretative task, that is, demonstrating that Thurman's thought is distinctively philosophical in its scope and methods. What I have tried to do is more analogous to what Gary Dorrien has accomplished apropos the theological or evangelical dimension in Thurman's thought, namely, to show that "Thurman called American Christianity to its best religious vision and in several ways exemplified it" (2003, 558), such that my complementary task consists in demonstrating how Thurman called-and continues to call-American philosophy, too, "to its best [philosophical] vision and in several ways exemplified it.""--